Ghosts of Transparency. Shadows cast and shadows cast out - Doyle, Michael R. (Applied Virtuality Book Series, 2019)
In this book, the editors focus on architecture and communication from various different perspectives - taking into account that the term "architecture" is used for buildings as well as in the context of computer software. Data and software also impact on our cities; raw data, however, do not convey any information - in order to generate information and communication they have to be organized and must make sense to the reader. The contributions avoid clear separation of the various communication spheres of their disciplines. Instead, they use the wide range of approaches to explore meanings - an ambitious aim that leaves the destination wide open; the reader is invited to share in this adventure.